Forest insect spectra in Late Holocene deposits of the Lena Delta Terrace, North of the actual tree line. - Kuzmina, Svetlana A; Bolshiyanov, Dimitry Yu (PANGAEA, 2002)
It was the first time that insects were sampled in the Late Holocene deposits of the Lena Delta. The insect fauna consists of taiga, aguatic and riparian, meadow, shrub, tundra and others species. There are many thermophilie species in different ecological groups of insects. Our findings suggest that about 3000 yr BP predominantly taiga or forest tundra with some steppe elements existed in eloser distance to the Lena Delta head in contrast to today. The climate was warmer than it is now and relative1y dry in this region.
Tab: 1: List of identified insect species in Lena Delta
Keywords: Bkh-B1; Bkh-B2s; Bkh-B3; Ecology; Family; Lena Delta, Siberia, Russia; ORDINAL NUMBER; OUTCROP; Outcrop sample; Part of body; Taxon/taxa